EFFECTIVITY OF SUPERVISION THEORY IN THE DEVELOPMENT OF EDUCATION - Nur Faizah; Sutiah Sutiah; Moh Muksit (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This study aims to explore the factors that influence the effectiveness of supervision in education, focusing on various theories of supervision such as clinical, formal, reflective, and transformational supervision. Using a qualitative research design with a case study approach, data were collected through in-depth interviews, participant observation, and document analysis in several schools. Thematic analysis was used to identify the main themes from the data obtained. The results of the study indicate that the effectiveness of supervision is influenced by the quality of communication between supervisors and teachers, a clear understanding of the purpose of supervision, and the competence of supervisors in providing constructive feedback. A supportive school context and culture are also very important for teacher professional development. A supervision approach that is tailored to the specific needs of schools and teachers has been shown to be effective in improving the quality of teaching and student learning outcomes. The implications of this study emphasize the importance of a holistic approach to supervision to achieve overall improvements in the quality of education. Recommendations for further research include longitudinal studies and exploration of the use of technology in supervision to support further teacher professional development.